SISTEM KENDALI OVER-HEAD CRANE DENGAN WIRELESS CONTROL MENGGUNAKAN SMARTPHONE ANDROID DAN TAMPILAN LCD BERBASIS ARDUINO - Bayu Sukma Sejati; Izza Anshory (Universitas Harapan Medan, 2019)
Overhead cranes are lifting tools used by almost all industries, ports, warehouses, workshops, and others. Generally, the overhead crane control system is less effective and efficient because the operator still follows where the crane is moving. In this case, problems often occur because the pendant switch that functions as a controller still uses the cable as a link to the overhead crane panel. Various problems that occur between cables often break up because of being hit by a load lifted by a hoist, operators who have difficulty adjusting the safe distance because they are limited by the length of the cable pendant switch. The purpose of this thesis is to create a control system that is expected to be able to control the overhead crane effectively and efficiently without using a cable as a connector but using an Android smartphone. Control with an Android smartphone using bluetooth serial communication with 16x2 LCD display and Arduino Uno R3 microcontroller. Based on the results of testing on this control system, control of the device can be controlled at a maximum distance of ± 12 meters without bulkhead and a distance of ± 10 meters with a bulkhead. The results of the test prove that the control system can function optimally and the remote application can be installed on the Android 4.0 Mininal Android smartphone (Jelly Bean). Therefore the use of cable can be replaced with a wireless connection system (Bluetooth) to reduce the occurrence of friction with the cable and so that the operator can maintain a safe distance with the load to be moved because it is not limited by the cable length